Complex Biophysical and Computational Analyses of G-Quadruplex Ligands: The Porphyrin Stacks Back - Satta, Giuseppe; Trajkovski, Marko; Cantara, Alessio; Mura, Monica; Meloni, Claudia; Olla, Giulia; Dobrovolná, Michaela; Pisano, Luisa; Gaspa, Silvia; Salis, Andrea; De Luca, Lidia; Mocci, Francesca; et al. (Chemistry (Weinheim an der Bergstrasse, Germany), 2024)
G-quadruplexes (G4 s), as non-canonical DNA structures, attract a great deal of research interest in the molecular biology as well as in the material science fields. The use of small molecules as ligands for G-quadruplexes has emerged as a tool to regulate gene expression and telomeres maintenance. Meso-tetrakis-(N-methyl-4-pyridyl) porphyrin (TMPyP4) was shown as one of the first ligands for G-quadruplexes and it is still widely used. We report an investigation comprising molecular docking and dynamics, synthesis and multiple spectroscopic and spectrometric determinations on simple cationic porphyrins and their interaction with different DNA sequences. This study enabled the synthesis of tetracationic porphyrin derivatives that exhibited binding and stabilizing capacity against G-quadruplex structures; the detailed characterization has shown that the presence of amide groups at the periphery improves selectivity for parallel G4 s binding over other structures. Taking into account the ease of synthesis, 5,10,15,20-tetrakis-(1-acetamido-4-pyridyl) porphyrin bromide could be considered a better alternative to TMPyP4 in studies involving G4 binding.
Keywords: simulace molekulární dynamiky; Molecular dynamics; Ligands; G-quadruplexes; G-kvadruplexy; cirkulární dichroismus; G-Quadruplexes; Molecular recognition; ligandy; simulace molekulového dockingu; Molecular Dynamics Simulation; porfyriny; Porphyrins; Circular Dichroism; NMR; DNA; Molecular Docking Simulation